Aman Abdurrahman: Ideologue and ‘Commander’ of IS Supporters in Indonesia - Vidia Arianti (Jurnal Ilmu Kepolisian, 2017)
On 10 January 2017 the United States designated Jamaah Ansharud Daulah (JAD) as a terrorist group and imposed sanctions on its leader Aman Abdurrahman, the leading ideologue and ‘commander’ of supporters of the ‘Islamic State’ (IS) terrorist group in Indonesia. Aman provided ideological and spiritual leadership for IS followers in Indonesia even before the group declared its so-called caliphate in June 2014. Many of his students joined IS ranks, conducted attacks in Indonesia or worked to unite various pro-IS groups under one umbrella. Imprisoned for the second time since 2010, Aman has been implicated in the January 2016 Jakarta attack. Despite his present incarceration and isolation, his sermons still resonate among IS followers in Indonesia.